Marketing Politik Dedi Mulyadi Sebagai Gubernur Jawa Barat di Media Sosial Youtube - Kusnandar, Alwi Rahman; Chomariah, Lailatul; Hakim, Lukman Rahman; Hafiz, Farhan Abdul; Harmonis, Harmonis; Fadhil, Mohammad Kesya; Khalaida, Safa (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study explores the political marketing strategy of Dedi Mulyadi through YouTube as a platform to promote his candidacy for Governor of West Java. It uses a qualitative descriptive method by analyzing the content of Dedi Mulyadi's official YouTube channel and how he communicates values, identities, and political narratives to build emotional ties with viewers. The findings show that Dedi Mulyadi successfully utilizes YouTube to build a populist, close-to-the-people image, emphasizing Sundanese cultural values and direct public engagement.